Associação da disfunção da musculatura abdutora do quadril com inclinação lateral do tronco na marcha de amputados - Enéas, Roberto Araújo (2022)
The purpose of this dissertation was to study the “association of dysfunction of the hip abductor musculature with lateral inclination of the trunk in the gait of amputees”. Lower limb amputations occur with greater incidence at the transtibial (TT) and transfemoral (TF) levels, and these individuals present muscle alterations, as in the case of the gluteus medius, which presents a deficit in strength. Amputees present variations in the gait pattern, with total lateral inclination (TLT) to the side of the prosthesis being the most common consequence. We carried out a pilot study with four individuals, two in each group. In addition, we wrote a review as a theoretical basis on the evolution in the evaluation of people with amputations from the perspective of the biopsychosocial model (study 1). After knowing the evolutionary evaluation process and defining the best tool to calculate ILT deviations, the objective of the main study was to investigate whether the level of amputation influences the function of the hip abductor musculature and the gait of people with unilateral lower limb amputation. The study included 23 individuals with unilateral lower limb amputation in two groups divided according to the level of amputation (TT vs TF). We evaluated hip abductor strength using isokinetic dynamometry and surface electroneuromyography (EMG) of the gluteus medius muscle, followed by ILT analysis. Differences in standardized means of the results of the TT vs TF groups were considered large for the variables in hip and trunk angles, strength for the non-amputee limb and EMG in the amputated limb. This implies that individuals in the TF group have greater hip and trunk angles and lower muscle strength in the non-amputated limb than those in the TT group. On the amputation side, the TF group had lower EMG signal values than the TT group. In intragroup comparisons for the amputated vs non-amputated sides, the amputated side had a higher ILT in both groups. The ILT angle of the non-amputated side, the EMG and strength of the amputated side are the most important variables to differentiate the TF and TT groups. We conclude that the function of the abductor musculature and the gait of individuals with TT and TF amputation suffer multifactorial influence beyond the level of amputation.